Two years of Functional Electrical Stimulation by large surface electrodes for denervated muscles improve skin epidermis in SCI - Giovanna Albertin; Helmut Kern; Christian Hofer; Diego Guidolin; Andrea Porzionato; Anna Rambaldo; Raffaele De Caro; Francesco Piccione; Andrea Marcante; Sandra Zampieri (PAGEPress Publications, 2018)
Our previous studies have shown that severely atrophic Quadriceps muscles of spinal cord injury (SCI) patients suffering with complete conus and cauda equina lesions, and thus with permanent denervation-induced atrophy and degeneration of muscle fibers, were almost completely rescued to normal size after two years of home-based Functional Electrical Stimulation (h-bFES). Since we used large surface electrodes to stimulate the thigh muscles, we wanted to know if the skin was affected by long-term treatment. Here we report preliminary data of morphometry of skin biopsies harvested from legs of 3 SCI patients before and after two years of h-bFES to determine the total area of epidermis in transverse skin sections. By this approach we support our recently published results obtained randomly measuring skin thickness in the same biopsies after H-E stain. The skin biopsies data of three subjects, taken together, present indeed a statistically significant 30% increase in the area of the epidermis after two years of h-bFES. In conclusion, we confirm a long term positive modulation of electrostimulated epidermis, that correlates with the impressive improvements of the FES-induced muscle strength and bulk, and of the size of the muscle fibers after 2-years of h-bFES.